Anxiogenic Effects of Acute Injection of Sesame oil May be Mediated by β-1 Adrenoceptors in the Basolateral Amygdala;-1 Adrenoceptors in the Basolateral Amygdala - Mahnaz Kesmati (Advanced Pharmaceutical Bulletin, 2014)
Purpose: A few studies have indicates that the sesame oil influences anxiety, but many reports show that β-1 adrenoceptors (ARs) of the basolateral amygdala (BLA) plays a pivotal role in this regard. Therefore, in this study the effect of acute injection of sesame oil on anxiety-like behavior in the presence and absence of the BLA β-1 ARs in the male Wistar rats were investigated. Methods: Guide cannulas, for seven groups of rats, were implanted bilaterally into the BLA. Two weeks after the stereotaxic surgery, anxiety-like behaviors (the OAT%, OAE % and locomotor activity) were evaluated by Elevated Plus-Maze (EPM) for all groups. 3 groups received different volumes of sesame oil (i.p.) and they were compared with control group (received saline via i.p.), and the anxiogenic volume of sesame oil (1.5ml/kg) was determined. Then, 3 other groups received constant effective volume of sesame oil (1.5ml/kg) along with 3 different doses of betaxolol, selective β-1 ARs antagonist, intra BLA microinjection in order to be compared with sesame oil group (1.5 ml/kg). Results: The acute injection of sesame oil with the volume dependent manner showed an anxiogenic effect with reduction of the OAT% and OAE% which the maximum effect of sesame oil was observed in the dose of 1.5mg/kg. Also, betaxolol with dose dependent manner attenuated the anxiogenic effects of sesame oil (1.5mg/kg), but this reduction could not remove the anxiety effects completely. Conclusion: It seems that the sesame oil acute (i.p.) injection induces anxiety, and this effect is attenuated by inhibition of β-1ARs in the BLA.